Spatial valuation of recreation activities in forest systems: application to province of Segovia (Spain) - Voces González, R.; Díaz Balteiro, L.; López-Peredo Martínez, E. (Forest Systems, 2010)
During the past few years there has been an important boost in the application of environment valuation techniques in forest ecosystems. In Spain, these studies have been characterized, among other features, by having been carried out in Protected Natural Areas and by not having included the spatial component of the territory. In this paper, it is aimed to make a valuation of the recreation activities for all the forest systems in a specific province (Segovia), integrating the space component by means of the CORINE Land Cover 2000 cartography. For that purpose, the results of 42 research works conducted in Spain have been taken, and, through a meta-analysis exercise, a model has been set up to estimate the willingness to pay for any recreation activity in the above forests. The model has different explanatory variables, including the inhabitants situated at a certain distance from the forest, the provincial income or the forest category associated with the CORINE polygon. The number of visitors has been obtained from the occupation degree of the accommodation in the rural dwellings of this province. Thus, the results obtained can be taken as being a low threshold of the recreation value associated with these ecosystems.